IDENTIFIKASI DAN PREVALENSI ENDOPARASIT PADA KAMBING DI KOTA PADANG, SUMATERA BARAT - Yufa, Marta; Mairawita, Mairawita; Herwina, Henny (Metamorfosa: Journal of Biological Sciences; Vol 5 No 1 (2018)DO - 10.24843/metamorfosa.2018.v05.i01.p14, 2018)
Goats are animals which are consumed by the community in the city of Padang. Goat population growth is not comparable with the numbers growing demand, it is because generally these goats reared traditionally small-scale ownership so that less maintenance and can cause goat easily attacked by the parasite. Purpose of this study are to identify of endoparasite that infected goats in Padang city and to determine the prevalence infection of each parasite. This study was conducted from April to May 2016 at five location in Padang city and continued in Animal Taxonomy Laboratory, Biology Department, Faculty of Mathematics and Natural Science, Andalas University. Faecal samples were collected from 25 goats. Faecal samples were examined using centrifugation-flotation methods. The results showed that two species endoparasites were found, those are Trichostrongylus sp. (prevalence value 64%) and one species Unidentified (sp. 1) from family Taeniidae (prevalence value 16%).